Pleiotropic functions of SscA on the asexual spore of the human pathogenic fungus Aspergillus fumigatus - Ye-Eun Son; Jiwoo Han; Kyung-Tae Lee; Hee-Soo Park (Mycology, 2024)
ABSTRACTAsexual spores, called conidia, are key reproductive fungal particles that enable survival in harsh environmental conditions or host systems. The conidia can infect humans, animals, and plants to cause various fungal diseases. Transcription factors, including VosA, WetA, and SscA, have key roles in conidia formation and long-term survival in Aspergillus nidulans. Herein, we report the pleiotropic functions of SscA in the conidia of the human pathogen A. fumigatus. The deletion of sscA increased conidia formation despite decreased fungal growth. Absence of sscA impaired long-term survival and reduced spore resistance to various stresses, including heat, UV, and oxidation. Transcriptomic analyses showed that SscA involved the mRNA expression of cell wall organisation-related genes. Importantly, the sscA deletion mutant conidia contained an increased amount of β-glucan and chitin compared to wild type conidia. In addition, conidial gliotoxin production was decreased in the sscA deletion strain. Overall, SscA has pleiotropic roles in conidia formation, maturation and dormancy and mycotoxin production in A. fumigatus.